Ethnoconcept Ukraine as a subject of cognitive mastering of the Universe (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article shows the cognitive mechanisms of development of the validity through verbalization of national marked concept Ukraine on a material of language clichés. Concept  Ukraine is meant by the highest level of ethnocentrism and it makes the national spiritual macroconcept. The background information sends recipient to the precendent situations, which are peculiar to Ukrainian culture.
Keywords: ethnoconcept; conceptual picture of the Universe; language clichés; cognitive base; ksenoethnonim